A new species of Acanthophyllum (Caryophyllaceae) from Iran - Pirani, Atefeh; Joharchi, Mohammad Reza; Memariani, Farshid (Phytotaxa, 2013)
The new species Acanthophyllum yasamin-nassehiae (Caryophyllaceae) from North Khorassan province (north-eastern Iran) is here described and illustrated. It belongs to the sect. Oligosperma, and it is related to A. lilacinum and A. brevibracteatum from the morphological point of view. Notes on its ecology and conservation status are given.